The Man Question : Male Subordination and Privilege. - Dowd, Nancy E. (NYU Press, 2010)
Among the many important tools feminist legal theorists have given scholars is that of anti-essentialism: all women are not created equal, and privilege varies greatly by circumstances, particularly that of race and class. Yet at the same time, feminist legal theory tends to view men through an essentialist lens, in which men are created equal. The study of masculinities, inspired by feminist theory to explore the construction of manhood and masculinity, questions the real circumstances of men, not in order to deny men's privilege but to explore in particular how privilege is constructed, and w.